Adaptation variation of easiness on environmental, social, and governance components in the selected sustainability developments - F.R. Sutikno; N.A. Sasongko; I.N. Djarot; H.S. Dillon (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Environmental, Social, and Governance reporting is universally recognized as a pivotal component embraced by the industry to address climate change and serve as a safeguard to the physical and social environments of society. In the absence of global standards, organizations have developed standardized reporting frameworks for companies. This study provides an adaptation easiness measurement and a wide range of environmental, social, and governance disclosure components extracted from several standards. Multiple standards and a broader range of scaling measurements were used in this study to observe the characteristics of each industry where each environmental, social, and governance component is specific. The objective of this study is to investigate how companies in Indonesia comply with various environmental, social, and governance standards, given the importance of identifying variations of easiness on environmental, social, and governance on sustainability reports.METHODS: Using multi-source analysis, content analysis, and exploratory data analysis, this study identified whether industries in Indonesia adopt selective patterns in the components included in their sustainability reports.FINDINGS: This study identified 26 environmental, 8 social, and 23 governance popular components, which are components with high environmental, social, and governance report applicability and company adaptability. The environmental components that is easy to adapt primarily center around formal environmental, social, and governance framework data, in social component revolves around customary practices in corporate social responsibility, and in governance component emphasizes corporate reputation. By employing industry-specific environmental, social, and governance components, this study identifies three distinct groups, enabling the formulation of tailored policies to effectively address the unique needs of each group.CONCLUSION: This study exposes several findings on how companies in Indonesia adopt different components of environmental, social, and governance reports according to their needs, regulations, and analysis complexity. The novelty of this study combined the use of unified comparison components, a wider range of scaling measurements, and specific environmental social, and governance components per-industry type.